Comparison of the simulated seismic behavior of small- and large-scale cripple walls: PEER-CEA Project test programs - Schiller, Brandon; Cobeen, Kelly; Hutchinson, Tara (Earthquake spectra, 2023)
As part of the Pacific Earthquake Engineering Research Center (PEER)-California Earthquake Authority (CEA) project, experimental programs were performed at UC San Diego and UC Berkeley, with the former focusing on small-component testing and the latter focusing on large-component testing. During the small-component testing program, a suite of 28 cripple wall-only specimens was tested under quasi-static reverse cyclic lateral loading with variations in exterior finishes, retrofit condition, cripple wall height, anchorage condition, boundary conditions, vertical load, and loading protocol. In the large-component testing program, cripple wall-first story specimens, load path connections, and combined materials in occupied stories were tested. The more easily performed small-component specimens facilitate comparison with the large-component specimens to allow the assessment of their potential to emulate large-scale specimen behavior, with a particular interest in cross-comparing their global hysteresis and physical damage evolution. This cross-comparison among small- and large-scale specimen test results is intended to offer best practices for the future design of cripple wall seismic retrofits in residential housing, with a particular interest in: (1) supporting the realistic design of small-component specimens that may capture the response of large-component specimens and (2) to qualitatively determine where the small-component tests fall in the range of lower- to upper-bound estimation of strength and deformation capacity for the purposes of numerical modeling. Data from both test programs were utilized in the PEER-CEA project to assist with validating numerical modeling tools, which in turn were used to generate seismic loss models capable of quantifying the reduction of loss achieved by applying state-of-practice retrofit methods as identified in FEMA P-1100 Vulnerability-Base Seismic Assessment and Retrofit of One- and Two-Family Dwellings. The objective of this article is to present an overview of the small- and large-component testing programs and key results pertaining to exterior finishes, boundary conditions, the FEMA P-1100 retrofit, and cripple wall height.